Towards creating a technology-enabled intervention to treat PTSD in military veterans - Ho, Layla (2018)
Traumatic stress caused as the result of a military career is a widely researched phenomenon. Posttraumatic Stress Disorder (PTSD) can develop when traumatic stress in individuals is not moderated and managed well. A wider variety of psychological interventions for treating PTSD have been researched since PTSD became a clinical diagnosis. However, with new and emerging technologies, as well as an increasingly technical and digital world, more research is needed to establish if technology can be successfully utilized in treating PTSD. The aim of this PhD was to investigate the perception and effectiveness of a technology-enabled intervention to help treat PTSD in UK military veterans. This intervention would take into account veteran experiences with interventions they have already undertaken. To achieve this, four studies were conducted overall. The first was a systematic review of the literature relating to individual psychological intervention for PTSD; a total of 11 studies were included in the review. The interventions from the 11 studies were broken down into three categories. Interventions across all studies were found to be effective. Further analysis of studies using military personnel as participants was conducted and found the CPT was the intervention method used to successfully reduce PTSD symptoms for this population. Analysis of studies which utilised technology to deliver the intervention was also conducted, all of these studies used Computerized Cognitive Behavioural Therapy to successfully reduce PTSD symptoms in the participants. The second study was qualitative research comprising semi-structured interviews with 12 veterans, asking questions on their perception of psychological treatment they had received for PTSD. The results showed that there were more positive opinions than negative opinions relating to the interventions that participants had experienced. However, all participants stated that they would be willing to try a technology-enabled intervention if it was available. The third study was a longitudinal study with a total of 98 participants taking part over a 27 month period. The aim of this longitudinal study was to establish the effectiveness of the technology-enabled intervention in reducing PTSD symptoms. The technology-enabled intervention was found to be significantly effective in reducing both PTSD symptoms overall and at a PTSD criterion level. The fourth and final study was qualitative research consisting of semi-structured interviews with 17 veterans. The questions asked related to their perceptions of the technology-enabled intervention experienced as a part of study three. Results showed that, overall, participants were satisfied that the intervention reduced their PTSD symptoms. However, there were some aspects of the intervention that they felt could have been better designed, including increasing the number of images in the intervention sessions or creating more interactive sessions. Overall, conclusions of the studies found that even though technology-enabled intervention were found to be effective at reducing PTSD symptom scores, there are improvements that can be made to increase its usability and effectiveness. Further research is required to improve the technology-enabled intervention, develop additional functionality and test its effectiveness in a randomised controlled trial.